Fourth Hankel Determinant for a Subclass of Starlike Functions Based on Modified Sigmoid. (16th December 2021) - Mashwani, Wali Khan; Ahmad, Bakhtiar; Khan, Nazar; Khan, Muhammad Ghaffar; Arjika, Sama; Khan, Bilal; Chinram, Ronnason
Abstract : In our present investigation, we obtain the improved third-order Hankel determinant for a class of starlike functions connected with modified sigmoid functions. Further, we investigate the fourth-order Hankel determinant, Zalcman conjecture, and also evaluate the fourth-order Hankel determinants for 2-fold, 3-fold, and 4-fold symmetric starlike functions.